Vitamin D Status of Very Low Birth Weight Neonates at Baseline and Follow-up after Daily Intake of 800 IU Vitamin D. (7th December 2020) - Choudhury, Khurshed Alam; Kumar, Mala; Tripathi, Shalini; Singh, S N; Singh, Kalpana; Singh, V K
Abstract : Introduction: Vitamin D deficiency (VDD) is rampant in neonates. Recommendations for supplementation are variable. Methods: An observational study was done on less than 32 weeks of very low birth weight neonates to find prevalence of VDD (<20 ng/ml) at baseline; at 38 ± 2 weeks post-menstrual age (PMA) after daily intake of 800 IU vitamin D (vit D). Secondary objectives were to find determinants of VDD, to compare growth in deficient; vit D sufficient (VDS) neonates; to find vit D toxicity. Results: Of 83 neonates, 81 (97.6%) were VDD at baseline and 5 (6%) at 38 ± 2 weeks PMA. Determinants for VDD at baseline were inadequate maternal sun exposure ( p  < 0.001) and vit D supplementation ( p  = 0.007). Factors for VDD at 38 ± 2 weeks PMA were male gender ( p  = 0.049), morbidities ( p  = 0.006), ventilation >24 h (<0.001), sepsis ( p  = 0.032), caffeine ( p ≤ 0.001) and missed supplements ( p < 0.001). Weight and length gain of VDD to VDS neonates were (6.70 ± 2.40 to 8.96 ± 2.21 g/day); (0.82 ± 0.34 to 1.08 ± 0.37 cm/week), respectively ( p  < 0.001). Head circumference gain (cm/week) of VDS; VDD neonates was 0.58 ± 0.09; 0.54 ± 0.06 ( p = 0.054), respectively. No neonates developed vit D toxicity. Conclusions: In preterm VLBW neonates, the prevalence of VDD was 97.6% but decreased by >90% at 38 ± 2 weeks with a daily intake of 800 IU vit D. Inadequate maternal vit D intake and sun exposure determined low baseline vit D status of neonates. Male gender, morbidities, ventilation, sepsis, caffeine, missed vitamin D supplements were determinants of poor vit D status at follow-up. Weight gain and length increments were more in the VDS group.